Unzureichende Ausschöpfung der Realsteuern: Das Beispiel Rheinland-Pfalz - Thomas Döring (Wirtschaftsdienst, 2018)
Zu den finanziellen Voraussetzungen kommunaler Selbstverwaltung zählt neben einer angemessenen Finanzausstattung über den kommunalen Finanzausgleich ebenso die hinreichende Ausschöpfung der originären Einnahmequellen durch Städte und Gemeinden. Dies steht sowohl in Einklang mit ökonomischen Effizienzüberlegungen als auch mit dem Subsidiaritätsgrundsatz und liefert den Ausgangspunkt dafür, die Realsteuerpolitik der Kommunen in Rheinland-Pfalz kritisch zu überprüfen. – – In Germany, state and local authorities repeatedly come into conflict with one another regarding the funding of municipal budgets. The sufficient fiscal endowment of local public authorities depends not only on a satisfactory provision of state grants but also requires an adequate exhaustion of existing sources of revenues at the local government level. Against this background, the paper analyses local tax policy in order to assess whether the budget fi nance potential is being sufficiently exploited. Taking Rhineland-Palatinate as a case study, the degree of tax exploitation (local business tax, local property tax) is empirically estimated fo r the time period 2009 to 2015.
Keywords: H71; H77; 330